2016
DOI: 10.1097/sga.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Foley Catheters as Temporary Gastrostomy Tubes

Abstract: Percutaneous endoscopic gastrostomy tube is the modality of choice for long-term enteral nutrition. In the event that replacement tubes are not available, urinary catheters can be used to maintain patency of the gastrostomy tract. This study reports our experience in a nurse-led service using Foley catheters as temporary gastrostomy tubes and the associated complications. Patients who had used Foley catheter as gastrostomy tube over a 2-year period (Jan 2011 to December 2012) were studied. Twenty-one patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
0
11
0
4
Order By: Relevance
“…Therefore, if dislodgment occurs after 4 weeks from initial placement, one can consider that the tract is mature and if a replacement balloon-type tube is available on site, this can be inserted through the pre-existing tract at the patient's bedside, without recourse to endoscopic visualization. If a replacement is not available and since the mature tract will start closing within the first 24 hours from tube dislodgment, the insertion of a temporary Foley catheter, in an attempt to keep the mature tract patent has been proposed [124,125]. However, the use of Foley catheters has been associated with high complication rates [125] and the evidence to recommend their use is considered to be of low quality [126].…”
Section: Tube Dislodgmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if dislodgment occurs after 4 weeks from initial placement, one can consider that the tract is mature and if a replacement balloon-type tube is available on site, this can be inserted through the pre-existing tract at the patient's bedside, without recourse to endoscopic visualization. If a replacement is not available and since the mature tract will start closing within the first 24 hours from tube dislodgment, the insertion of a temporary Foley catheter, in an attempt to keep the mature tract patent has been proposed [124,125]. However, the use of Foley catheters has been associated with high complication rates [125] and the evidence to recommend their use is considered to be of low quality [126].…”
Section: Tube Dislodgmentmentioning
confidence: 99%
“…If a replacement is not available and since the mature tract will start closing within the first 24 hours from tube dislodgment, the insertion of a temporary Foley catheter, in an attempt to keep the mature tract patent has been proposed [124,125]. However, the use of Foley catheters has been associated with high complication rates [125] and the evidence to recommend their use is considered to be of low quality [126]. In the case that replacement tube position is uncertain, direct endoscopic verification or use of a water-soluble contrast facilitated "tubogram" should be used to confirm the position.…”
Section: Tube Dislodgmentmentioning
confidence: 99%
“…However, the use of percutaneous endoscopic gastrostomy (PEG) and nasogastric tubes (NGT) were the two most common enteral devices reported in the literature. Studies have shown that NGT was frequently used in patients who required short‐term ETF, whereas PEG was more commonly used among patient who required long‐term ETF (Arribas et al., ; Metussin, Sia, Bakar, & Chong, ).…”
Section: Introductionmentioning
confidence: 99%
“…5 We found no relevant statistics, but a current review of published literature (PubMed since inception, using "foley catheter" AND gastrostomy) revealed 38 publications in the English language which indicate that Foley catheters were being used worldwide as temporary gastrostomy tubes and that their use for prolonged periods (median 15 months) was acceptable and cost-effective. 6 Short-term trials of Foley catheters have yielded safety data comparable to commercial gastrostomy tubes 5 , but our patient case is a reminder of the ease of a catheter being "swallowed" unless properly cared for and fixated, and the need for emergency physicians to be aware of these potential complications which may not be apparent on presentation and to also consider "wandering" tube in the differential diagnosis of obstruction or ileus in the elderly.…”
Section: Discussionmentioning
confidence: 83%